Psychology of accident victims in India: explorations in embodiment, suffering and healing - Sharma, Deepika (Critical and qualitative approaches to mental health, 2023)
This book traces the psychological journey of accident survivors with locomotor disability, as they move from processes of suffering to healing. It provides a holistic understanding of disability by looking into the embodied understanding of the body as shaped by the socio-political and cultural discourses around impairment